Characteristics and Influencing Factors of Phosphorus Loss in Watersheds during Typical Rainfall Events - LIU Xiao-rong, DU Xin-zhong, LIU Xin-ru, HAN Yu-guo, AN Miao-ying, LEI Qiu-liang, LIU Hong-bin (长江科学院院报)
[Objective] Surface runoff and soil erosion during rainfall events are the main drivers of phosphorus (P) loss in watersheds, particularly during the rainy season when a few key heavy rainfall events can dominate annual phosphorus load outputs. However, the characteristics of phosphorus loss, influencing factors, and lag effects during different intensities of typical rainfall events in the rainy season remain to be further explored. This study aims to understand the characteristics and influencing factors of phosphorus loss under various magnitudes of typical rainfall events and to analyze the phosphorus loss process during dominant rainfall events. [Methods] During the 2022 and 2023 rainy seasons, five rainfall events (E1-E5) of varying intensities were monitored at the outlet of the Fengyu River sub-watershed, a typical agricultural watershed in the Erhai Lake Basin, Yunnan Province. The rainfall types for events E1-E5 were moderate rain, light rain, moderate rain, heavy rain, and heavy rain. A total of 265 water samples were collected to determine three forms of phosphorus: total phosphorus (TP), total dissolved phosphorus (DP), and particulate phosphorus (PP). Redundancy analysis was used to explore the relationships between phosphorus concentrations/loads and rainfall-runoff characteristics, identifying the key factors influencing phosphorus output and its process. Lag analysis was applied to reveal the hydrological processes behind phosphorus loss. [Results] The results indicated that: (1) The trends of TP and PP concentrations were consistent with flow changes across different types of rainfall events. (2) Total rainfall, rainfall duration, peak flow, and maximum 30-minute rainfall intensity were positively correlated with phosphorus concentrations, while antecedent rainfall index was negatively correlated. (3) Particulate phosphorus dominated the phosphorus loss during rainfall events, accounting for 67%-93% of the total. (4) There was no uniform lag effect between TP, PP, and DP concentrations and discharge. TP and PP shared similar lag effects, indicating that phosphorus primarily originated from surface runoff. [Conclusion] Changes in phosphorus concentrations during rainfall events are influenced by rainfall magnitude, intensity, and antecedent soil conditions. Concentrations and loads of all phosphorus forms were strongly correlated with rainfall duration, total rainfall, peak flow, and 30-minute maximum intensity (I30). The relationship between nutrient concentration and discharge is jointly determined by total rainfall, rainfall duration, antecedent conditions, and hydrological regime. By identifying the characteristics of phosphorus output under various rainfall events during the rainy season, this study provides insights into phosphorus load contributions and supports the control of phosphorus pollution and eutrophication in watershed water bodies.